The invention of the inspired text: philological windows on the Theopneustia of scripture - Poirier, John C. (Library of New Testament studies, 2020)
List of Tables Preface Abbreviations -- Chapter 1-Is ?All Scripture ? Inspired?? The Meaning of Theopneustia in 2 Timothy 3:16 -- Chapter 2-Pre-Origen Uses of Theopneustia -- Chapter 3-Pre-Origen Uses of Theopneustia -- Chapter 4-Excursus: Theopneustia in the Physiologus and the Cyranides -- Chapter 5-Inspirationism and the New Testament -- Chapter 6- The Screw Turns: Theopneustia in Irenaeus, Clement of Alexandria, Tertullian, the De Universo (of Hippolytus?), and Origen -- Chapter 7- Post-Origenist Traces of a Vivificationist Understanding of Qeo&pneustoj in Nonnus of Panopolis -- Chapter 8- In Lieu of a Conclusion: Inspirationism's Waning as a Blessing in Disguise-The Truth of the Gospel versus the ?Truth? of the Scriptures in Evangelical and Postliberal Hermeneutics Bibliography Index